Bank Sentral dan Lingkungan Politik Ekonomi: Pengalaman Indonesia - Fachry Ali (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2016)
A central bank should be performing in the political-economy arena that so often is in situation between conflict and harmony. Because of that, it's not surprising that we often catch a fact that not only the mone- tary policies are theoretically drawn with technical calculations in which it would be more frequently evaluated politically, but also the authority of political authoritarianism so often suspect the motivation behind the mo- netary policy, and hence tend to control it.The experience of central bank in Indonesia under the transition from New Order to Reformasi era could become the historical lesson for our state and society.